Manajemen Sumber Daya Manusia Berbasis Pendidikan Pondok Pesantren - Ritonga, Anas Habibi; Jamil, Muhammad; Harvius, H.; Mukhlishin, Ahmad (Jurnal Penelitian, 2018)
Human resource management works in the area of an organization's processes and policies by managing the human resources in it. Islamic boarding schools are da'wah and da'wah institutions that require HRM to achieve their expected goals. A strategy is needed to achieve the intended goals, including setting the direction of the organization, making environmental analysis, formulating strategies, implementing starategi, and evaluating. The presentation in this report uses the Preliminary formation, discussion and closing. Data collection uses a qualitative-descriptive and analysis-critical approach. Data sources are extracted from the literature relating to the formulation of the problem.